2009
DOI: 10.1088/0029-5515/49/6/065029
|View full text |Cite
|
Sign up to set email alerts
|

Study of ion turbulent transport and profile formations using global gyrokinetic full-f Vlasov simulation

Abstract: A global gyrokinetic toroidal full-f five-dimensional Vlasov simulation GT5D (Idomura et al 2008 Comput. Phys. Commun. 179 391)is extended including sources and collisions. Long time tokamak micro-turbulence simulations in open system tokamak plasmas are enabled for the first time based on a full-f gyrokinetic approach with self-consistent evolutions of turbulent transport and equilibrium profiles. The neoclassical physics is implemented using the linear Fokker-Planck collision operator, and the equilibrium r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
191
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 153 publications
(210 citation statements)
references
References 44 publications
(96 reference statements)
19
191
0
Order By: Relevance
“…(9a) either in Vlasov code with a finite velocity grids or in Monte Carlo code with a finite number of simulation markers. Then an iterative operation of the field-particle operator is usually taken in simulation codes [8,20] to reduce the numerical error, but it is time consuming. In FORTEC-3D, the accuracy of collision operator is improved by solving the factors (a, b, c) as functionals of (δn, δP, δE) instead of using their theoretical values given by Eq.…”
Section: Fortec-3d Codementioning
confidence: 99%
See 3 more Smart Citations
“…(9a) either in Vlasov code with a finite velocity grids or in Monte Carlo code with a finite number of simulation markers. Then an iterative operation of the field-particle operator is usually taken in simulation codes [8,20] to reduce the numerical error, but it is time consuming. In FORTEC-3D, the accuracy of collision operator is improved by solving the factors (a, b, c) as functionals of (δn, δP, δE) instead of using their theoretical values given by Eq.…”
Section: Fortec-3d Codementioning
confidence: 99%
“…Recent progress in theory and simulation studies of plasma transport processes now turn their attention to the combination of these two models that can treat multi-scale transport phenomena ranging from O(ρ i ) to O(L T,n ). Idomura et al [8] has developed a gyrokinetic simulation code GT5D which includes neoclassical physics by adopting the full-f approach and introducing a conserved form linear Fokker-Planck collision operator [9,10]. In the simulation study of ion-temperature-gradient (ITG) turbulence transport by GT5D, it is found that the shear of the equilibrium radial electric field dE r /dr plays a critical role in dictating the directions of avalanche propagation and non-diffusive momentum transport.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the field equation is in that case solved with an iterative solver whose convergence is not guaranteed and depends on the physical problem. For these reasons, many of the global gyrokinetic codes [23,11,12,13] still solve the field equation on the poloidal plane with direct solvers. The GT3D code [23] uses a ballooning phase factor to extract analytically the k = 0 structure at a given magnetic surface: the grid resolution of the field equation can be strongly reduced.…”
Section: Introductionmentioning
confidence: 99%